Both sides of the equation must be multiplied by 1/cd to give the following equation: b = a/cd
- The following equation was given in this question: a = bcd. This means that a = b × c × d.
- Hence, to make "b" the subject of the formula, we have to eliminate "cd" from the side of the equation with "b". To do that, we multiply both sides of the equation with the same expression as follows:
a x 1/cd = bcd x 1/cd
- "cd" cancels out "cd" in the right side of the equation to result to:
a/cd = b
Therefore, b = a/cd
Learn more: https://brainly.com/question/21866313